Academic Procrastination Among Peruvian University Students: Its Relationship With the use of Virtual Academic Media, Adaptation to University Life, and Social Media Addiction - Quispe-Figueroa, Orfa Lizet (2026)
Introduction. The research objective was to determine whether the use of virtual academic media, adaptability to university life, and addiction to social media are associated with academic procrastination in Peruvian university students. Method. The design used was predictive and cross-sectional, which allows analyzing relationships at a single point but does not permit causal inferences. 581 university students from public and private institutions in the country were surveyed, mostly between 18 and 25 years old (86.4%), male (57.3%), mainly from private universities (54.0%) and from the mountain region (74.5%). The instruments used were the Scale of Use of Virtual Academic Media, Adaptability to University Life, Addiction to Social Media, and Academic Procrastination. Results. The structural model showed an adequate fit to the data (CMIN/DF = 1.031, CFI = 0.960, SRMR = 0.044, RMSEA = 0.037). Social media addiction (β = 0.10, p < 0.001) and adaptability to university life (β = 0.11, p < 0.001) were significantly associated with academic procrastination, whereas the use of virtual academic media was not significant (β = −0.04, p > 0.05). The model explained 9% of the variance in academic procrastination (R² = 0.09). Conclusions. Furthermore, the resulting model showed that adaptability to university life and social media addiction were significantly associated with academic procrastination, whereas the use of virtual academic media was not significantly related.